Effects of sowing methods on nitrogen compounds and protease activities of whole‐crop wheat silage - Liuxing Xu; Guojian Tang; Dan Wu; Jianguo Zhang (Grassland Research, 2023)
Abstract Background Whole‐crop wheat (Triticum aestivum) has high nutritive value, and it has become one of the main sources of roughage for ruminants in some countries or regions. This study investigates the effects of no tillage on nitrogen compounds and protease activities of whole‐crop wheat silage. Methods Wheat was planted on the 9th day (NB9) and 5th day (NB5) before rice harvest and on the first day after rice harvest. Sowing before harvest involved no tillage and sowing after rice harvest involved either no tillage (NA1) or conventional tillage (CK). Results Compared to CK, the crude protein content of NB9 and NB5 decreased by 16.4% and 9.58%, respectively. With the delay of the sowing date, the contents of non‐protein nitrogen, rapidly degraded protein, and slowly degraded protein in whole‐plant wheat tended to increase. Compared to NA1 wheat silage, the NH3‐N content of NB9 and NB5 silages decreased by 52.7% and 34.4%, respectively. The acid protease activity of NA1 was significantly higher than that of other treatments (p < 0.05). Conclusions There was no significant difference in the degree of protein degradation between NA1 and CK silages. Although the degree of protein degradation in early sowing was low, the degree of fermentation was also weak.